PENGEMBANGAN PENYEDAP RASA ALAMI DARI CANGKANG RAJUNGAN DENGAN METODE FOAM-MAT DRYING - Diode Yonata; Nurhidajah Nurhidajah; Boby Pranata; Muhammad Yusuf (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Swimming crab shells have been confirmed as umami source food waste. Information regarding the use of swimming crab shells in making seasoning in very limited. Processing the swimming crab shells into flour will cause the shell protein to hydrolyze, so that amino acids become free and give an umami effect derived from glutamic acid compounds. Umami compounds from crab shell flour can be developed into seasoning along with components of salt, sugar and pepper. This research to determine the best formula for making natural seasoning from swimming crab shells using the foam-mat drying method. A total of 5 formulas were determined based on the ratio of swimming crab shell flour to salt, that is F1 (25:45), F2 (30:40), F3 (35:35), F4 (40:30) and F5 (45:25). The parameters analyzed included physical and chemical characteristics of seasoning. The results showed that the higher addition of swimming crab shell flour had an effect on increasing levels of glutamic acid as a source of umami and the rendement of seasoning, as well as decreasing salt content, water content, solubility, and product hygroscopicity, but did not affect sugar content and water activity of the seasoning. The best formula for seasoning is F4 with a ratio of swimming crab shell flour to salt (40:30).